2010
DOI: 10.1093/nar/gkq643
|View full text |Cite
|
Sign up to set email alerts
|

The phosphatase interactor NIPP1 regulates the occupancy of the histone methyltransferase EZH2 at Polycomb targets

Abstract: Polycomb group (PcG) proteins are key regulators of stem-cell and cancer biology. They mainly act as repressors of differentiation and tumor-suppressor genes. One key silencing step involves the trimethylation of histone H3 on Lys27 (H3K27) by EZH2, a core component of the Polycomb Repressive Complex 2 (PRC2). The mechanism underlying the initial recruitment of mammalian PRC2 complexes is not well understood. Here, we show that NIPP1, a regulator of protein Ser/Thr phosphatase-1 (PP1), forms a complex with PP1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(74 citation statements)
references
References 36 publications
8
66
0
Order By: Relevance
“…The cell lines expressed the fusions in a doxycycline (Dox)-dependent manner and to a similar extent (Figs S1A and S2A). As expected (Tanuma et al, 2008;Van Dessel et al, 2010), EGFP traps of the NIPP1-Wt and NIPP1-Fm fusions showed an association with endogenous PP1, which was not seen with the NIPP1-Pm and NIPP1-Fm+Pm fusions (Figs S1B and S2B). The associated PP1 was inactive with glycogen phosphorylase as substrate but the phosphatase activity could be revealed by trypsinolysis, which destroys NIPP1 but not PP1 (Beullens et al, 1998), confirming that NIPP1-Wt and NIPP1-Fm inhibit PP1 (Fig.…”
Section: The Overexpression Of Nipp1 Causes An Arrest In Mitosis and supporting
confidence: 77%
See 2 more Smart Citations
“…The cell lines expressed the fusions in a doxycycline (Dox)-dependent manner and to a similar extent (Figs S1A and S2A). As expected (Tanuma et al, 2008;Van Dessel et al, 2010), EGFP traps of the NIPP1-Wt and NIPP1-Fm fusions showed an association with endogenous PP1, which was not seen with the NIPP1-Pm and NIPP1-Fm+Pm fusions (Figs S1B and S2B). The associated PP1 was inactive with glycogen phosphorylase as substrate but the phosphatase activity could be revealed by trypsinolysis, which destroys NIPP1 but not PP1 (Beullens et al, 1998), confirming that NIPP1-Wt and NIPP1-Fm inhibit PP1 (Fig.…”
Section: The Overexpression Of Nipp1 Causes An Arrest In Mitosis and supporting
confidence: 77%
“…Anti-GAPDH and anti-cleaved caspase 3 antibodies were purchased from Cell Signaling Technology, and anti-BubR1 and antiKif18A antibodies from Bethyl laboratories. The anti-NIPP1 and anti-PP1 antibodies were made in-house, as previously described (Van Dessel et al, 2010). Anti-Sap155, anti-cyclin B1, anti-γ-H2Ax, anti-Aurora B, anti-Aca and anti-Flag antibodies were purchased from MBL International, BD Pharmingen, Millipore, BD Transduction Laboratories, ImmunoVision (Springdale, AR) and Stratagene, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…73 It has been demonstrated that several factors are involved in PRC2 recruitment to target genes. The serine/threonine protein phosphatase-1 (PP1), along with its regulatory partner NPP1, is able to modulate the DNA occupancy of EZH2 and its activity, enabling or reducing EZH2 phosphorylation; 74,75 Twist-1, in mesenchymal stem cells (MSCs), recruits EZH2 at the ARFINK4a locus, inducing transcriptional repression of both p14 and p16; 76 PHF1, another PcG protein, influences the recruitment and enzymatic activity of PRC2. 77,78 Additionally, recent studies demonstrated that the protooncogene n-Myc is able, in neuroblastoma, to recruit EZH2 at clusterin promoter, inducing the silencing of this tumor suppressor gene and promoting tumorigenesis.…”
Section: Recruitment Of Prc2 To Target Genesmentioning
confidence: 99%
“…siRNA mediated suppression of PP1 was achieved as described previously (27). The following siRNA sense olgonucleotide sequences were used: Control, 5′-UAAGGCUAUGAAGAGAUACdTdT-3′; PP1α, 5′-CCGCAUCUAUGGUUUCUACdTdT-3′; PP1λ, 5′-GC AUGAUUUGGAUCUUAUAdTdT-3′.…”
Section: Suppression Of Pp1 Expression With Double-stranded Rna (Sirna)mentioning
confidence: 99%